Analysis of factors that influence teacher commitment at the ABC Foundation - Oktavianti, Ita; Wanasida, Albert Surya (Enrichment : Journal of Management, 2024)
Teachers play a crucial role in shaping individuals' attitudes and mentality. Therefore, it is essential to ensure their work commitment. This study investigates the impact of transformational leadership, organizational culture, work environment, and job satisfaction on the organizational commitment of 131 teachers at ABC Foundation, using a quantitative approach with SEM-PLS analysis. Results indicated that transformational leadership, work environment, and job satisfaction have a significant positive impact on teachers' work commitment. However, organizational culture did not have a significant effect. Additionally, the study found that transformational leadership, organizational culture, and work environment have a significant positive impact on job satisfaction. The influence of transformational leadership, organizational culture, and work environment on work commitment was not significantly mediated by job satisfaction